Debiasing Framing Effects in Auditors' Internal Control Judgments and Testing Decisions* - EMBY, CRAIG; FINLEY, DAVID (Contemporary Accounting Research, 1997)
Abstract. This paper reports the results of an experiment examining the framing bias and a potential debiasing technique. Practicing auditors formed a judgment about a hypothetical client's inventory internal control system to determine the amount of related substantive testing. Auditors from two Big Six firms were randomly assigned to one of four treatments in a fully crossed 2 times 2 between‐subjects design. The initial description of the internal control system was identical for all treatments, as were the items of additional evidence about the system. Auditors either judged the risk of the control system or the strength of the control system. The risk‐strength frames were crossed with two levels of debiasing technique: “none” or “evidence rating.” Results indicate that without debiasing, significant framing effects were present, but that evidence rating significantly mitigated the framing effect. In this auditing context, the framing bias appears to be easily induced, but is not robust. Although the profession should be aware of this potential problem, effective remedial or proactive steps can be easily implemented and may naturally occur in current practices.